2019
DOI: 10.3390/s19183963
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy Composites with Reduced Graphene Oxide–Cellulose Nanofiber Hybrid Filler and Their Application in Concrete Strain and Crack Monitoring

Abstract: Advances in nanotechnology have provided approaches for the fabrication of new composite materials for sensing. Flexible sensors can make up for the shortcomings of traditional strain sensors in monitoring the surface strain and cracks of concrete structures. Using reduced graphene oxide (RGO) as a conductive filler, cellulose nanofiber (CNF) as a dispersant and structural skeleton, and waterborne epoxy (WEP) as a polymer matrix, a flexible composite material with piezoresistive effect was prepared by the solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…When concrete is stressed, its resistivity will change obviously, and its resistance is sensitive to the stress response. According to resistivity change, the stress of smart GNPC can be inferred, and thus the intelligent response can be realized [108][109][110]. Wu et al [108] found that graphene nanofibers can form a stable conductive network, resulting in a considerable change in the resistivity of the composite.…”
Section: Field Response Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…When concrete is stressed, its resistivity will change obviously, and its resistance is sensitive to the stress response. According to resistivity change, the stress of smart GNPC can be inferred, and thus the intelligent response can be realized [108][109][110]. Wu et al [108] found that graphene nanofibers can form a stable conductive network, resulting in a considerable change in the resistivity of the composite.…”
Section: Field Response Mechanismmentioning
confidence: 99%
“…According to resistivity change, the stress of smart GNPC can be inferred, and thus the intelligent response can be realized [108][109][110]. Wu et al [108] found that graphene nanofibers can form a stable conductive network, resulting in a considerable change in the resistivity of the composite. e curve of Figure 21(a) shows a good linear relationship between RCR and strain in the strain range of about 10%.…”
Section: Field Response Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…CCMs with piezoresistive properties have demonstrated great potential in developing smart civil engineering structures with the capability of self-sensing and structural health monitoring. For example, such CCMs with a piezoresistive property can be used in buildings and infrastructures to monitor the strain and crack in the structures [116,117]. Therefore, the improvement in the piezoresistive property of the GRCCMs can significantly enhance the sensitivity of such multifunctional composites as sensors.…”
Section: Piezoresistive Propertymentioning
confidence: 99%
“…The choice of curing temperature is the key to the formation of a stable reinforcement and conductive network. If the temperature is high and the water evaporates too quickly, the network between graphene flakes will be destroyed, thus affecting the mechanical and electrical properties of the composites [24]. Table 1 is the filler percentage of samples, and the values of RGO and CNF are mass percent to WEP.…”
Section: Materials and Instrumentsmentioning
confidence: 99%